Large variations in the practice patterns of surgical antiseptic preparation solutions in patients with open and closed extremity fractures: a cross-sectional survey - Maria Jurado-Ruiz; Gerard P. Slobogean; Sofia Bzovsky; Alisha Garibaldi; Nathan N. O’Hara; Andrea Howe; Brad Petrisor; Sheila Sprague (Antimicrobial Resistance and Infection Control, 2018)
Abstract Background Surgically-managed fractures, particularly open fractures, are associated with high rates of surgical site infections (SSIs). To reduce the risk of an SSI, orthopaedic surgeons routinely clean open fracture wounds in the emergency department (ED) and then apply a bandage to the open wound. Prior to the surgical incision, it is standard practice to prepare the fracture region with an antiseptic skin solution as an additional SSI prevention strategy. Multiple antiseptic solutions are available. Objectives To explore the variation in practice patterns among orthopaedic surgeons regarding antiseptic solution use in the ED and antiseptic preparatory techniques for fracture surgery. Methods We developed a 27-item survey and surveyed members of several orthopaedic associations. Results Two hundred and-ten surveys were completed. 71.0% of respondents irrigate the open wound and skin in the ED, primarily with saline alone (59.7%) or iodine-based solutions (32.9%). 90.5% of responders indicated that they dress the open wound in the ED, with 41.0% applying a saline-soaked bandage and 33.7% applying an iodine-soaked dressing (33.7%). In their surgical preparation of open fractures, 41.0% of respondents used an iodine-based solution, 26.7% used a chlorhexidine gluconate (CHG)-based solution, and 31.4% used a combination of the two. In closed fractures, 43.8% of respondents used a CHG-based solution, 28.1% used an iodine-based solution, and 27.1% used a combination. Despite theoretical concerns about the use of alcohol in open wounds, 51.4% used alcohol-based solutions or alcohol alone during skin preparation of open fractures. Conclusions A lack of consensus exists regarding use of antiseptic surgical preparation solutions for fractures. High-quality clinical research is needed to assess the effectiveness of different surgical antiseptic preparation solutions on patient outcomes in fracture populations.